2020
DOI: 10.1530/erc-20-0135
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine kinase inhibitor therapy and metabolic remodelling in papillary thyroid cancer

Abstract: The present study used [18F]FDG-PET to study glucose metabolism and tumor responses for thyroid cancer xenografts expressing the glycolytic pathway modulators platelet-derived growth factor receptor (PDGFR) and BRAFV600E. PET data were correlated with immunohistochemistry staining and kinetic analysis for facilitative glucose transporter 1 (GLUT1) and hexokinase-II (HK2). Vemurafenib decreased [18F]FDG uptake in BCPAP cells in vitro; however, it was increased by ~70% with imatinib application to BCPAP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…High rate of glycolysis is mainly related to increased cellular glucose uptake in cancer cells. More and more evidence showed that abnormal glucose metabolism is closely related to the occurrence and development of thyroid cancer [ 7 , 8 ]. Moreover, thyroid cancer cells with higher malignancy also featured with stronger glycolytic activity [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…High rate of glycolysis is mainly related to increased cellular glucose uptake in cancer cells. More and more evidence showed that abnormal glucose metabolism is closely related to the occurrence and development of thyroid cancer [ 7 , 8 ]. Moreover, thyroid cancer cells with higher malignancy also featured with stronger glycolytic activity [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The in vitro experiments also revealed that thyroid cancer cells with BRAF V600E (BCPAP and 8505C cells) are more glycolytic than those without via HIF1α-MYC-peroxisome proliferator-activated receptor γ coactivator 1β (PGC1β) axis [29,57], and that glucose uptake is suppressed by vemurafenib, a BRAF inhibitor, in BCPAP cells having BRAF V600E [29,54]. Of interest, Lee et al have found localization of BRAF V600E not only in the cytoplasm but also in mitochondria in PCCl3-BRAF V600E cells.…”
Section: Glucose Metabolism Reprogramming In Thyroid Cancersmentioning
confidence: 95%
“…In the in vitro experimental settings, growth of eight human thyroid cancer cell lines, including 8505C, K18, C643, TPC1, etc., is largely dependent on glucose [51]. Compared to Nthy-ori 3-1 cells, an immortalized normal human thyroid cell line, BCPAP and TPC1 cells are more glycolytic, as demonstrated by higher glucose uptake, LDH production and expression levels of GLUT1 and HK1/2, although their mitochondrial function is intact [31,[52][53][54]. LDHA knockdown (KD) and overexpression decreases and increases the migration and invasion of these cells, respectively.…”
Section: Glucose Metabolism Reprogramming In Thyroid Cancersmentioning
confidence: 99%
“…However, glucose uptake and metabolism in thyroid tumor cells were downregulated when BRAF V600E was blocked by vemurafenib. In terms of tumor growth, combination therapy of imatinib and vemurafenib was much more effective than single therapy and led to a near abolition of the tumors ( 158 ). The combination of imatinib and HK2 inhibitors may solve the problem of drug resistance and also provide better efficacy in TC.…”
Section: Prognostic Biomarkers and Treatmentmentioning
confidence: 99%